Cytogenetic, chromosome count optimization and automation of Neolamarckia cadamba (Rubiaceae) root tips derived from in vitro mutagenesis - Wee Hiang, Eng; Wei Seng, Ho; Kwong-Hung, LING (Horticulture and Forestry Society from Transylvania, 2021)
Chromosome count is the only direct way to determine the number of chromosomes of a species. This study is often considered trivial that seldom described and discussed in detail. Therefore, it is inevitable that the chromosome count protocol should be revised and revisited before it becomes obliterated. In the present study, we encountered challenges in obtaining a clear micrograph for the chromosome count of active mitotic cells of Neolamarckia cadamba (Roxb.) Bosser (Rubiaceae) root tips. Several obstacles were determined through micrograph observation, such as existing unwanted particles in cells, poor chromosome staining and chromosome clumping. To overcome these, root tip types, staining methodologies, squashing methods were among the factors assessed to obtain clear micrographs. The chromosome counts of N. cadamba under optimized procedure showed 2n = 44 chromosomes. We also apply digital technology in chromosome counts, such as online databases and graphic software that are open source and freely accessible to the public. Only basic laboratory equipment and chemicals were used throughout the study, thus making this study economical and applicable in a basic laboratory. The availability of online digital software and databases provide open-source platforms that will ease the efforts in chromosome count.